The Impact of Pagergunung Embung Sekembang Tourism Destination on The Income of Pagergunung Village Communities, Ngablak Sub-District, Magelang District - Wulan Pradita; Luluk Ul Fatul Diroh; Yeni Priatnasari (Islamic Accounting Journal, 2022)
This study aims to analyze the impact of the Papergunung Sekembang Embung tourist destination for the income of the surrounding community. The method used in this study is a mixed method, using quantitative and qualitative data. The respondent in this study was the community around the Embung. The research data processing technique uses simple linear regression analysis techniques. The result of the study showed that dewarm tourism destinations had a significant impact on community income.Keywords: Tourist Influence, Income, Local Communities, Impact